Phosphatase and Phytase Secreting Efficiency of Some Multipurpose Trees of Arid Region - Yadav, B K; Tarafdar, J C (Annals of Arid Zone, 2016)
Eight tree species were compared for the activity of root associated androot released acid phosphatase and phytase to select the best tree species to exploitnative unavailable P for better nutrition. The activity of root associated acid phosphataseand phytase of all genotypes was about 7 to 10 times higher than that of rootreleased acid phosphatase and phytase and the tree species performed differentlywith regard to the activity of the enzymes. P deficiency increased significantly(P